2012
DOI: 10.1038/bcj.2011.49
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular characterization of early T-cell precursor leukemia: a high-risk subgroup in adult T-ALL with a high frequency of FLT3 mutations

Abstract: A subgroup of pediatric acute T-lymphoblastic leukemia (T-ALL) was characterized by a gene expression profile comparable to that of early T-cell precursors (ETPs) with a highly unfavorable outcome. We have investigated clinical and molecular characteristics of the ETP-ALL subgroup in adult T-ALL. As ETP-ALL represents a subgroup of early T-ALL we particularly focused on this cohort and identified 178 adult patients enrolled in the German Acute Lymphoblastic Leukemia Multicenter studies (05/93–07/03). Of these,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
102
3
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(118 citation statements)
references
References 62 publications
10
102
3
3
Order By: Relevance
“…5,6 This immature cluster shows a high level of enrichment of transcripts that are associated with early thymic precursor (ETP)-ALL, 22 a subgroup of T-ALL that exhibit a stem cell/immature myeloid-like immunophenotype, resistance to treatment and poor outcome. 15,[23][24][25][26] Genomic analysis of ETP-ALL has revealed high rates of mutations in factors involved in cytokine receptor and RAS signaling, hematopoiesis and epigenetic modification, 15 but the precise molecular basis of these patients' adverse prognosis remains unclear.…”
Section: An Early Thymic Precursor Phenotype Predicts Outcome Exclusimentioning
confidence: 99%
“…5,6 This immature cluster shows a high level of enrichment of transcripts that are associated with early thymic precursor (ETP)-ALL, 22 a subgroup of T-ALL that exhibit a stem cell/immature myeloid-like immunophenotype, resistance to treatment and poor outcome. 15,[23][24][25][26] Genomic analysis of ETP-ALL has revealed high rates of mutations in factors involved in cytokine receptor and RAS signaling, hematopoiesis and epigenetic modification, 15 but the precise molecular basis of these patients' adverse prognosis remains unclear.…”
Section: An Early Thymic Precursor Phenotype Predicts Outcome Exclusimentioning
confidence: 99%
“…Recent genetic studies have shed new light on the biology of early T cell precursor acute lymphoblastic leukemia (ETP-ALL), a distinct disease entity associated with poor prognosis and defined by a characteristic immunophenotype and a gene expression signature indicative of a very early arrest in T cell development (24) . N eumann M et al has also identified this as a high risk subtype of T ALL expressing a high rate of FLT3 mutation in adults (25) Molecular studies in pediatric CD34…”
Section: Discussionmentioning
confidence: 99%
“…[62][63][64][65] Like acute myeloid leukemia, most ETP ALL harbor mutations that activate RAS and RAS pathway components. 63,65,66 JAK1 and JAK3 are also commonly mutated in ETP ALL.…”
Section: Discussionmentioning
confidence: 99%